2014
DOI: 10.1177/1099800414523118
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Sleep in 10 Bedridden Elderly Patients With Disorders of Consciousness in a Japanese Hospital

Abstract: No previous study has satisfactorily clarified the nature of sleep in elderly bedridden people with disorders of consciousness (DOC). The objective of the present study was to clarify the sleep states of 10 elderly bedridden patients with DOC in a Japanese hospital to facilitate provision of evidence-based nursing care and appropriate adjustment of patients' environments. Nocturnal polysomnography recordings were analyzed according to the standard scoring criteria, and the patients' sleep stages and quality we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 25 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…In the previously discussed [23]. Similar findings have been demonstrated in previous investigations of patients with severe brain injuries [20,21,32]. Furthermore, slow wave sleep has been linked to learning and memory and is thought to have an important role in synaptic homeostasis [46,47].…”
Section: Slow Wave Sleepsupporting
confidence: 84%
See 1 more Smart Citation
“…In the previously discussed [23]. Similar findings have been demonstrated in previous investigations of patients with severe brain injuries [20,21,32]. Furthermore, slow wave sleep has been linked to learning and memory and is thought to have an important role in synaptic homeostasis [46,47].…”
Section: Slow Wave Sleepsupporting
confidence: 84%
“…Overall, patients diagnosed as being in a minimally conscious state tend to exhibit more preserved sleep architecture than patients diagnosed as being in a vegetative state (unresponsive wakefulness syndrome) [16][17][18][19]. Further, slow wave sleep correlates with more overt signs of awareness in most of these patients [20][21][22][23]. The circadian rhythms of patients with chronic disorders of consciousness are quite variable, with reports of periods ranging from 6 to 63 h in one study [24] and 23-26 h in another study [25].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, a statistically significant difference in age-related sleep quality was not confirmed (F = 0.1; p = 0.736). The impact of age was evaluated in the studies of the authors (Matsumoto et al, 2015;Sterniczuk et al, 2014), who, on the basis of the results, suggest that stages of sleep change in people aged 60 years and more, and there is a higher incidence of sleep-related respiratory disorders and abnormal movements related to sleep, and subjectively impaired sleep quality. The sociological analysis sought to examine the relationship between sleep quality perception in patients in ICU from the gender perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Bedridden people are permanently bound to bed (Hirakawa et al, 2005;Matsumoto et al, 2015;Morimoto et al, 2006;Tanaka et al, 2013;Urasaki et al, 2011) and cannot sit up (Sugimoto et al, 2004) or get out of bed independently (Tseng et al, 2007).…”
Section: Screeningmentioning
confidence: 99%
“…• Sleep disturbances Matsumoto et al, 2015) • High risk of shoulder pain (Fullerton et al, 2003), and hand injury (e.g. carpal tunnel syndrome) (Wick & Zanni, 2007) due to using a manual wheelchair for locomotion • Infections (due to all microbes on wheelchair rims and tires with transfer from hand to face, eyes and nose) in particular in people with immune deficiencies (Wick & Zanni, 2007) • Shoulder and back pain (due to an inadequate proper skeletal and postural alignment in a wheelchair sitting position) (Veneman et al, 2017;Wick & Zanni, 2007) • High risk of pressure ulcer (Hampton, 2011;Urasaki et al, 2011;Wick & Zanni, 2007) • Respiratory changes (due to poor posture that the lungs may not fully expand) (Wick & Zanni, 2007) • High risk of falling (due to an inadequate proper skeletal and postural alignment) (Veneman et al, 2017) • Muscular atrophy (Wick & Zanni, 2007) • Dysphagia (due to a poor posture that disrupts normal swallowing) (Tamura et al, 2002;Wick & Zanni, 2007) • Fatigue (due to a poor position or seating that makes activities difficult) (Wick & Zanni, 2007) • Injuries (due to ill-fitting wheelchairs or a lack of wheelchair training) (Wick & Zanni, 2007) Physical consequences:…”
Section: Consequences Of Being Wheelchair-bound Consequences Of Being...mentioning
confidence: 99%